Perkembangan Koperasi Syariah di Era Digital: Tantangan dan Peluang - Nashiha, Merlly; Apriliansyah, Ega; Putra Nur Falah, Alip; Hidayatullah, Kikin (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
The development of sharia cooperatives in Indonesia has undergone significant transformation alongside the rapid advancement of digital technology, which has reshaped how people conduct transactions and interact. In recent years, the sharia cooperative sector has experienced considerable growth, driven particularly by changes in societal behavior that increasingly prioritize the use of digital platforms in various economic activities. This study aims to analyze the challenges and opportunities faced by sharia cooperatives in navigating the digital era. Using a qualitative research approach through a literature review of various relevant journals and reports, the study explores factors influencing the development of sharia cooperatives and how these cooperatives can leverage digital technology to enhance efficiency and competitiveness. The findings reveal that digitalization can expand market access, improve operational efficiency, and support service innovation. However, challenges such as limited technological understanding among members and regulatory barriers remain significant hurdles. The study concludes that sharia cooperatives must undergo digital transformation with a structured strategy to ensure sustainability and competitiveness. Keywords: Sharia Cooperatives, Digitalization, Challenges, Opportunities